2008
DOI: 10.1177/104063870802000311
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Four Commercial Enzyme-Linked Immunosorbent Assays for the Diagnosis of Bovine Paratuberculosis in Chilean Dairy Herds

Abstract: Abstract. The accuracy of 4 commercial enzyme-linked immunosorbent assays (ELISAs) for diagnosis of bovine paratuberculosis was compared using sera from 53 Mycobacterium avium subsp. paratuberculosis (MAP) fecal culture-positive dairy cows (cases) and sera from 345 dairy cattle resident in 11 fecal culturenegative herds on 2 consecutive occasions 1 year apart (controls). The specificity of all 4 ELISA kits was .99%, and their diagnostic sensitivity ranged from 30.2% to 41.5%. Pairwise comparison of ELISAs foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
2
19
0
4
Order By: Relevance
“…Collectively, both that study and the current study demonstrate that recombinant proteins tested thus far do not improve upon commercially available ELISAs. However, there are many more candidates remaining to be tested, and in all cases, they must be measured against commercially available tests, which serve as the standard that they must surpass (12).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, both that study and the current study demonstrate that recombinant proteins tested thus far do not improve upon commercially available ELISAs. However, there are many more candidates remaining to be tested, and in all cases, they must be measured against commercially available tests, which serve as the standard that they must surpass (12).…”
Section: Discussionmentioning
confidence: 99%
“…Son yıllarda yüksek sensitivite ve spesifite ile özellikle seroprevalans çalışmalarında ELISA hemen hemen kullanılan tek yöntem gibi görünmektedir [4][5][6]11,19] . Yapılan çalışmalarda ELISA'nın sensitivite değeri %30.2-%51.0, spesifite değeri ise %95 ile %99 arasında değiştiği belirtilmiştir [4,5,17,19,20] . Fakat son yıllarda geliştirilen ticari kitlerde sensitivitenin %74.1'e kadar çıktığı ve spesifite oranının ise %99'un üstünde olduğu bildirilmiştir [4,17,19,20] .…”
Section: Tartişma Ve Sonuçunclassified
“…Yapılan çalışmalarda ELISA'nın sensitivite değeri %30.2-%51.0, spesifite değeri ise %95 ile %99 arasında değiştiği belirtilmiştir [4,5,17,19,20] . Fakat son yıllarda geliştirilen ticari kitlerde sensitivitenin %74.1'e kadar çıktığı ve spesifite oranının ise %99'un üstünde olduğu bildirilmiştir [4,17,19,20] . Prospektüse göre, araştırmamızda kullanılan ELISA kitinin sensitivite ve spesifite oranları sırasıyla %64.7 ve %99.2 olarak belirtilmiştir.…”
Section: Tartişma Ve Sonuçunclassified
“…Among tests to detect serum antibody to MAP, ELISAs are the most widely used. Several commercial ELISA kits for bovine PTB are currently available, and multiple studies have compared their accuracy [9, 10]. Comparative studies of ELISAs with different antigens have shown discrepancies in the ability of these tests to identify all infected animals [11].…”
Section: Introductionmentioning
confidence: 99%